Biologically active additives in the 21st century: undenatured type II collagen as an example of good medical practice - I. S. Dydykina; D. A. Dibrov; K. S. Nurbaeva; P. S. Kovalenko; A. A. Kovalenko (Современная ревматология)
The paper deals with an update on biologically active additives (BAAs) and emphasizes their role in normalizing and/or improving the functional status of organs and systems, including the gastrointestinal tract microflora, in reducing the risk of diseases, etc. It gives data on the consumption and turnover of BAAs, definitions and classifications of this group of substances, the basic documents governing the control of their production and promotion in different countries and in Russia. Undenatured type II collagen (UC-II® ) that is made from the chicken sternal cartilage and is a component of Sustaflex is considered as an example of the BAA that is compliant with good medical practice regulations. The therapeutic properties of UC-II® have been confirmed in clinical trials. The paper describes the mechanism of action of the BAA, evidence for its efficacy and safety, and the possibility of its administration for the prevention and combination treatment of knee osteoarthritis (OA) and its use as an alternative treatment for OA.